2006
DOI: 10.2746/042516406x159034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conformation on orthopaedic health and performance in a cohort of National Hunt racehorses: preliminary results

Abstract: Studies of the effects of conformation on performance and risk of injury may aid in identifying individuals likely to perform well on the racecourse and avoid risks of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 21 publications
3
62
2
Order By: Relevance
“…The two geometrical centers of these lines were connected and the length of MP measured from the proximal articular surface to the distal articular surface of MP (line "c"). Although in the study by Weller et al [5] showed that the dorsal MCP angle was significantly different between sound horses and horses suffering from SDFT lesions, in the present study, no association between dorsal MCP joint angle and the presence of SDFT lesions was found. The difference of our results to those of Weller et al [5] may be because of the different population of horses studied.…”
Section: Length Of Mpcontrasting
confidence: 74%
See 2 more Smart Citations
“…The two geometrical centers of these lines were connected and the length of MP measured from the proximal articular surface to the distal articular surface of MP (line "c"). Although in the study by Weller et al [5] showed that the dorsal MCP angle was significantly different between sound horses and horses suffering from SDFT lesions, in the present study, no association between dorsal MCP joint angle and the presence of SDFT lesions was found. The difference of our results to those of Weller et al [5] may be because of the different population of horses studied.…”
Section: Length Of Mpcontrasting
confidence: 74%
“…These results were predominantly attributed to sire effect and indicated significant heritability [2]. Among other results, Weller et al [5] found that an increased dorsal MCP joint angle and an increased carpus valgus conformation increased the risk of SDFT injury in National Hunt horses. An earlier study on Thoroughbred racehorses found a clinically relevant association between hoof angle ratios and incidence of effusion of the carpus and risk of effusion in the hind fetlock.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The repeatability of the gait variables included in this study has previously been determined in young growing pigs (Stavrakakis et al, 2013a). The range of mean differences between marker placements was comparable to achievement in horses (Weller et al, 2006) and humans (Maynard and Bakheit, 2003), including both stance and swing phases of the gait cycle. Although skin movement has been found to be increased during the swing phase (van Weeren et al, 1992), the joint angles during this phase undergo substantial changes, as confirmed in the current study where pigs showed a greater range of motion.…”
Section: Discussionmentioning
confidence: 87%
“…Such studies may focus on the long-term effects of those gait parameters with a small within-subject value, indicating higher individual consistency, in a population displaying greater between-subject variety that is higher CVs. Weller et al (2006) describe the long-term effects of individual gait patterns on orthopaedic health in horses.…”
Section: Discussionmentioning
confidence: 99%